Passive Sampling as a Tool to Assess Atmospheric Pesticide Contamination Related to Vineyard Land Use - Stéphan Martin; Marie-Hélène Dévier; Justine Cruz; Geoffroy Duporté; Emmanuelle Barron; Juliette Gaillard; Karyn Le Menach; Patrick Pardon; Sylvie Augagneur; Pierre-Marie Flaud; Éric Villenave; Hélène Budzinski (Atmosphere, 2022)
The massive use of pesticides in agriculture has led to widespread contamination of the environment, particularly the atmospheric compartment. Thirty-six pesticides, most used in viticulture, were monitored in ambient air using polyurethane foams as passive air samplers (PUF-PAS). Spatiotemporal data were collected from the samplers for 10 months (February–December 2013), using two different sampling times (1 and 2 months) at two different sites in a chateau vineyard in Gironde (France). A high-volume active air sampler was also deployed in June. Samples were extracted with dichloromethane using accelerated solvent extraction (ASE) (PUFs from both passive and active) or microwave-assisted extraction (MAE) (filters from active sampling). Extracts were analyzed by both gas and liquid chromatography coupled with tandem mass spectrometry. A total of 23 airborne pesticides were detected at least once. Concentrations in PUF exposed one month ranged from below the limits of quantification (LOQs) to 23,481 ng PUF−1. The highest concentrations were for folpet, boscalid, chlorpyrifos-methyl, and metalaxyl-m—23,481, 17,615, 3931, and 3324 ng PUF−1. Clear seasonal trends were observed for most of the pesticides detected, the highest levels (in the ng m−3 range or the µg PUF−1 range) being measured during their application period. Impregnation levels at both sites were heterogeneous, but the same pesticides were involved. Sampling rates (Rs) were also estimated using a high-volume active air sampler and varied significantly from one pesticide to another. These results provide preliminary information on the seasonality of pesticide concentrations in vineyard areas and evidence for the effectiveness of PUF-PAS to monitor pesticides in ambient air.